Explaining Continuance Intention in Artificial Intelligence-Supported Learning through Artificial Intelligence Literacy and Technology Acceptance Model - Muhammad Nur Faiz; Muhammad Yahya; Abdul Muis Mappalotteng; Sanatang; Fathahillah; Fitria Arifyanti; Selen Subasi (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – Despite the growing use of artificial intelligence in higher education, prior studies have focused more on initial adoption than on continuance intention, while the role of AI literacy in sustaining AI use remains underexplored. This study examines an integrative model linking AI literacy, perceived usefulness, attitude toward using AI, behavioral intention, and continuance intention in AI-supported learning.Methods – A quantitative cross-sectional survey was conducted with 324 students from the Educational Informatics and Computer Engineering and Computer Engineering programs at Universitas Negeri Makassar. Data were collected from January to February 2025 using a 25-item Likert-scale questionnaire and analyzed with PLS-SEM in SmartPLS 4 using bootstrapping with 10,000 subsamples.Findings – All hypothesized relationships were significant: AI literacy → perceived usefulness (β = 0.449, p < 0.001), AI literacy → attitude toward using AI (β = 0.177, p < 0.001), perceived usefulness → attitude toward using AI (β = 0.686, p < 0.001), attitude toward using AI → behavioral intention (β = 0.757, p < 0.001), and behavioral intention → continuance intention (β = 0.800, p < 0.001). Research implications – The cross-sectional design, self-reported data, purposive sampling, and single-institution context limit causal inference and broader generalizability.Originality – This study extends TAM by positioning AI literacy as a competence-based antecedent within a post-adoption sequence that explains continuance intention through perceived usefulness, attitude, and behavioral intention. Practically, the findings suggest that sustainable AI integration in higher education requires not only access to AI tools but also structured support for students’ AI literacy.